2021
DOI: 10.1002/jum.15728
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Step Strategy for Optimizing the Preoperative Classification of Adnexal Masses in a University Hospital, Using International Ovarian Tumor Analysis Models

Abstract: Objectives To evaluate the performance of a two‐step strategy compared with the International Ovarian Tumor Analysis (IOTA) ‐ Assessment of Different NEoplasias in the adneXa (ADNEX) model for preoperative classification of adnexal masses. Methods An ambispective diagnostic accuracy study based on ultrasound data collected at one university hospital between 2012 and 2018. Two ultrasonographers classified the adnexal masses using IOTA Simple Rules (first step). Not classifiable masses were evaluated using the I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Two or more papillary projections (n: 21) were found in malignant masses (n: 13) most of them with vascularization (n: 8), and in eight cases of benign lesions, five of them cystoadenofibromas ( Figure 4 ). Cystadenofibromas are sometimes difficult to classify [ 23 , 24 , 31 ] as they can appear most commonly as a unilocular solid cyst with papillary projections [ 32 , 33 , 34 ]. Other authors suggested that the presence of acoustic shadows behind a papillae can distinguish cystadenofibromas from other malignant masses, specially borderline tumors [ 16 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two or more papillary projections (n: 21) were found in malignant masses (n: 13) most of them with vascularization (n: 8), and in eight cases of benign lesions, five of them cystoadenofibromas ( Figure 4 ). Cystadenofibromas are sometimes difficult to classify [ 23 , 24 , 31 ] as they can appear most commonly as a unilocular solid cyst with papillary projections [ 32 , 33 , 34 ]. Other authors suggested that the presence of acoustic shadows behind a papillae can distinguish cystadenofibromas from other malignant masses, specially borderline tumors [ 16 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, IOTA developed the Simple Rules Risk assessment (SRR) based on SR 10 ultrasonic features and center types using logistic regression analysis. Besides, other imaging or ultrasound models have been proposed to address these masses, such as MRI, contrast-enhanced ultrasound (CEUS), the Risk of Malignancy Index (RMI), the Risk of Malignancy Algorithm (ROMA), the Assessment of Different NEoplasias in the adneXa (ADNEX) model [27][28][29][30] . A previous study [31] also exploited a logistic regression model based on SR and CA125 and validated the value.…”
Section: Discussionmentioning
confidence: 99%
“…ADNEX model can not only distinguish the probability of benign and malignant AMs, but also distinguish between www. journals.viamedica.pl/ginekologia_polska borderline ovarian tumors, stage I ovarian cancer, stage II-IV ovarian cancer, and secondary metastatic ovarian cancers, which includes three clinical features and six ultrasound features [4,[11][12][13]. Ovarian-adnexal Reporting and Data System (O-RADS) [14] and management system published by the American College of Radiological is modeled after IOTA and aims to provide consistent interpretation, reduce or eliminate ambiguity in ultrasound diagnosis, and provide management recommendations for each risk category.…”
Section: Introductionmentioning
confidence: 99%